Beauty in life: An eye‐tracking study on young adults' aesthetic evaluation and vitality judgment of pictorial representations of sleeping and dead subjects. Issue 4 (25th April 2019) - Di Dio, Cinzia; Massaro, Davide; Savazzi, Federica A.; Gallese, Vittorio; Garau, Tiziana; Gilli, Gabriella; Marchetti, Antonella
Abstract: Preferring life to death is deeply rooted in our biology. With the present study, we explored two questions: (1) Can this inclination be transposed to aesthetics, so that a living being is valued as more beautiful than a non‐living being? and (2) Are there any differences in the visual exploration of portrayals of a living compared to a dead human? In particular, are there any specific facial features representing the vitality status of a living or dead subject? By answering both questions, young adults' eye gazing was analyzed while they observed, aesthetically judged, and judged the vitality status of faces extracted from paintings representing a sleeping or dead subject. The aesthetic preference for the stimuli as a function of vitality (living, dead) was assessed both during the eye‐tracking study and during a follow‐up priming behavioral experiment. The analysis of the responses given during the aesthetic judgment task in the eye‐tracking study revealed preference for the sleeping compared to the dead subjects, supporting proclivity to attribute greater aesthetic value to living beings. This evidence was substantially confirmed by the follow‐up priming behavioral study, which further showed a significant effect of explicit vitality labeling on the aesthetic evaluation of the portrayals of sleeping subjects. As far as the visual exploration of the stimuli is concerned, the main eye‐tracking results revealed great attention to the eye region of both sleeping and dead subjects, which was particularly enhanced for the sleeping compared to the dead subjects. For the latter stimuli, focused attention was also found to the mouth region. These results are discussed in light of different theoretical proposals, including the "embodied" theory of aesthetic perception based on the existence of mirror systems.